Correlates of lake use by breeding common scoters in Scotland. Issue 4 (9th December 2015) - Hancock, Mark H.; Robson, Hannah J.; Smith, Trevor D.; Douse, Andy
Abstract: 1. Many populations of sea‐ducks, which typically winter at sea but breed on fresh water, are declining. Numbers of common scoters Melanitta nigra (L.) breeding in Scotland halved between 1995 and 2007, despite most breeding sites having special conservation status. To identify potential conservation measures, a 3‐year study was conducted, investigating correlates of lake use by scoters. 2. At 26 scoter breeding lakes, food abundance (macroinvertebrates) and foraging habitats (substrates, water depth) were measured, and their associations with scoter lake use explored using multi‐model inference. Correlates of macroinvertebrate abundance (water quality, fish abundance) were also investigated. 3. Averaged over 3 years (2009–2011), these lakes held 26.7 (SE 6.3) females, around half the Scottish breeding population. Scoters occurred more often at lakes having abundant large‐bodied invertebrates and extensive shallow water. Lakes where the average weight of the largest invertebrate in each sample exceeded 4 mg had 9.2 times (females) or 27 times (broods) more scoter records than other lakes. Lakes where water depths (10 m from the shore) averaged less than 1.3 m had 2.5 times (females) or 12 times (broods) more scoter records than other lakes. 4. The abundance of large‐bodied invertebrates was greater where small fish species (mostly three‐spined sticklebacks Gasterosteus aculeatus ) were more common and brown trout Salmo trutta were scarcer. 5. Results suggest two approaches to scoter conservation. At lakes used for hydro‐electricity generation, water level regimes that provide extensive shallow water should be tested to see if these benefit scoters. At lakes used for trout fishing, trout reduction by increased angling should be trialled, to see if this increases large‐invertebrate abundance and scoter use. Copyright © 2015 John Wiley & Sons, Ltd.